Dementia key gene identification with multi-layered SNP-gene-disease network - Lee, Dong Gi; Kim, Myungjun; Son, Sang Joon; Hong, Chang Hyung; Shin, Hyunjung (Bioinformatics, 2020)
Motivation: Recently, various approaches for diagnosing and treating dementia have received significant attention, especially in identifying key genes that are crucial for dementia. If the mutations of such key genes could be tracked, it would be possible to predict the time of onset of dementia and significantly aid in developing drugs to treat dementia. However, gene finding involves tremendous cost, time and effort. To alleviate these problems, research on utilizing computational biology to decrease the search space of candidate genes is actively conducted. In this study, we propose a framework in which diseases, genes and single-nucleotide polymorphisms are represented by a layered network, and key genes are predicted by a machine learning algorithm. The algorithm utilizes a network-based semi-supervised learning model that can be applied to layered data structures.
Keywords: Algorithms; Computational Biology; Dementia; Gene Regulatory Networks; Humans; Supervised Machine Learning